Characterization of patients with IgA nephropathy with and without associated minimal change disease - Guo, Wei-yi; Sun, Li-jun; Dong, Hong-rui; Wang, Guo-qin; Xu, Xiao-yi; Cheng, Wen-rong; Zhao, Zhi-rui; Ye, Nan; Liu, Yun; Cheng, Hong (Frontiers in Nephrology, 2023)
Introduction Immunoglobulin A nephropathy (IgAN) presents various clinical manifestations and pathological phenotypes. Approximately 5% of patients with IgAN present with early onset nephrotic syndrome, mild mesangial lesions, and diffuse foot process effacement of podocytes, which resemble minimal change disease (MCD). These patients are defined as MCD-IgAN. Whether MCD-IgAN is a special type of IgAN or simply MCD accompanied by IgA deposition remains controversial. Methods A total of 51 patients diagnosed with MCD-IgAN at Beijing Anzhen Hospital from January 2010 to September 2022 were recruited. The clinical and pathological characteristics of IgA-MCD were analyzed. Patients with IgAN but without MCD (non-MCD-IgAN) and healthy participants were enrolled as controls. Galactose-deficient immunoglobulin A1 (Gd-IgA1) and complement C3 were detected both in the circulation and in renal tissues. Results We found that the levels of serum Gd-IgA1 were lower in participants with MCD-IgAN than in those with non-MCD-IgAN, but higher than in healthy participants. Gd-IgA1 was rarely deposited in the glomeruli of participants with MCD-IgAN, with a positive rate of only 13.7% (7/51); in contrast, the positive rate in participants with non-MCD-IgAN was 82.4% (42/51). Among renal Gd-IgA1-positive patients, Gd-IgA1 and immunoglobulin A (IgA) colocalized along the glomerular mesangial and capillary areas. Interestingly, we found that the circulating levels of complement C3 were significantly higher in participants with MCD-IgAN than in participants with non-MCD-IgAN. In addition, the intensity of C3c in glomeruli in participants with MCD-IgAN was significantly weaker than in participants with non-MCD-IgAN. Conclusions Our study suggests that, in MCD-IgAN, most of the IgA that is deposited on glomeruli is not the same pathogenic Gd-IgA1 as found in general IgAN. Complement activation both in the circulation and in the renal locality was much weaker in MCD-IgAN than in non-MCD-IgAN. Our study suggests that IgAN with MCD might be MCD with coincidental IgA deposition.